2006
DOI: 10.1111/j.1540-6210.2006.00656.x
|View full text |Cite
|
Sign up to set email alerts
|

Unequal Pay: The Role of Gender

Abstract: Despite years of equal opportunity and affi rmative action eff orts, women remain concentrated in certain lower-level positions. In a study of the federal senior service, Mani (1997) noted that women occupied 85 percent of all clerical positions but only 13 percent

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
106
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(114 citation statements)
references
References 33 publications
7
106
1
Order By: Relevance
“…For example, Marini (1989) found that discrimination may be based on race or gender and be manifested in lower compensation, fewer possibilities to attain management or higher positions and fewer promotion opportunities. Similarly, Alkadry and Tower (2006) found that among women and men in similar positions in an organisation and in the same field of work, compensation differences occur for various reasons, including gender. Cocchiara, Bell, and Berry (2006) analysed the salary gap among Latina women and black women compared to white men and men of the same ethnic group.…”
Section: Perceptions Of Discrimination In Compensation and Distributimentioning
confidence: 94%
See 1 more Smart Citation
“…For example, Marini (1989) found that discrimination may be based on race or gender and be manifested in lower compensation, fewer possibilities to attain management or higher positions and fewer promotion opportunities. Similarly, Alkadry and Tower (2006) found that among women and men in similar positions in an organisation and in the same field of work, compensation differences occur for various reasons, including gender. Cocchiara, Bell, and Berry (2006) analysed the salary gap among Latina women and black women compared to white men and men of the same ethnic group.…”
Section: Perceptions Of Discrimination In Compensation and Distributimentioning
confidence: 94%
“…People tend to be treated and/ or compensated differently depending on the social group to which they belong The International Journal of Human Resource Management 2251 (Hang-yue et al 2003). Those belonging to lower status groups are more likely to be victims of prejudice, negative stereotypes and discrimination in organisations than those belonging to groups of a higher status or position (Alkadry & Tower, 2006). Various studies have analysed differences in income among minorities and working women.…”
Section: Perceptions Of Discrimination In Compensation and Distributimentioning
confidence: 99%
“…The first type of studies uses archival data to observe numerical differences between groups of employees or to analyze claims of discrimination. An example of this is Llorens, Wenger, and Kellough (2008) who investigate the representation of women and racial minorities in the public sector in the U.S.. Related, Alkadry and Tower (Alkadry & Tower, 2006, 2011 look at gender wage differences as an indication of discrimination. Another example is Leasher and Miller (2012) who use discrimination claims filed in Ohio to explore difference between public and private sector workplaces.…”
Section: Employment Discriminationmentioning
confidence: 99%
“…OFCCP 1 defines the salary discrimination as different treatment to individuals with similar skills and qualifications in job and responsible hierarchy. And gender salary discrimination refers to that female employees receive less salary than their male peers as a result of organization custom or enterprise policy, even if these female employees do the same job, have the same educational background and experience as their male peers (Alkadry, 2006).…”
Section: Salary Gender Discriminationmentioning
confidence: 99%